PENGARUH PENERAPAN MEDIA GAMBAR TERHADAP KETERAMPILAN MENULIS PUISI PESERTA DIDIK KELAS IV SD NEGERI MENCOBALANG II KABUPATEN GOWA - Natasya, Fitrah Sri; Marjuni; Djafar, Hamsiah; Halimah, Andi; Saleh, Chairati (Primer Edukasi Journal, 2025)
This thesis aims to: (1) To determine students' poetry writing skills before implementing photographic image media in Class IV of Moncobalang II State Elementary School, Gowa Regency. (2) To determine students' poetry writing skills after implementing photographic image media in class IV of Moncobalang II State Elementary School, Gowa Regency. (3) To determine the differences in students' poetry writing skills before and after the application of image media in class IV of Moncobalang II State Elementary School, Gowa Regency. This research is based on an approach, namely quantitative research. The type of research used is pre-experimental research, with a one-group pretest-posttest design. The results of descriptive data analysis show that the average value of the reality of writing poetry for students before implementing photographic image media was 64.33. Meanwhile, the average score for students' poetry writing skills after applying photographic image media was 91.67. The results of data analysis using the t-test showed that the percentage value in the category was 86.7% and the low category reached 13.3%. This shows that there is a positive influence on the results of students' poetry writing skills at SD Negeri Moncobalang II, Gowa Regency before and after the application of photographic image media. With the results of the paired sample t-test, it can be seen that a significance value (2-tailed) of 0.000 was obtained. The significance value obtained is smaller than ???? (0.000 < 0.05). So it can be said that there is a significant difference between before and after the application of photographic image media and it can be said that Ho is rejected and Ha is accepted.